Brain structural complexity and life course cognitive change - Nazahah, Mustafa; Ahearn, Trevor S.; Waiter, Gordon D.; Murray, Alison D.; Whalley, Lawrence J.; Staff, Roger T. (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/